Kualitas Layanan Kantor Imigrasi Kelas 1 Yogyakarta dalam Pembuatan Paspor Berbasis E-Government - Iswahyudi Iswahyudi; Ulung Pribadi (Universitas Muhammadiyah Yogyakarta, 2014)
The porpuse of the research is to determine the quality of servicein the government apparatus based electronicpassport, in this study using 5 indicators that Keberwujudan (tangible), Daya Tanggap (Responsiviness), Kehandalan(Realibility), Jaminan (Assurance), and Empathy (Empathy). andalsosee at the factors that influence the quality ofservice indicators Organizations, Human Resource, and Service System. The methoduse disdescriptive quantitativemethod using frequency distribution, and the data collection were interviews, observation, documentationandquestionnaires. With research sites at the Immigration Office Class 1 Yogyakarta. Results ofthe research is thatthequality of service in thegovernment apparatus based electronic passport given tothe publicis VeryGood”as indicatedby the scale 4.21cumulative indexofthe highest value 5.The variables that have the highest value is in thevariable Assurance (Warranty) with a score value of 4.60 with the category of “Very Good” and the variable that getsthe lowest score by the public is the variable empathy with a score value of 3.97although the category of “Good”. Asfor the factor of influence in the organization’s services are among the factors, for cesor human resources andservice system. Then there commendations givent o the immigration office in Yogyakarta is in grade 1 to furtherenhancethe quality of His ministry, especially in the Empathy dimension of hospitality, courtesy and discriminatoryactions in serving.